FIRST YEAR UNIVERSITY STUDENTS’ CONCEPTUAL UNDERSTANDING OF PHYSICAL AND CHEMICAL CHANGES (A Preliminary Research) - Syahrial Syahrial; Sri Winarni (Chimica Didactica Acta, 2021)
The purpose of this study is to identify first year university students' understanding of the concepts of physical and chemical changes. This study involved 43 students from the 2019 batch of the Chemical Education Study Program (PSPK) of the Faculty of Science and Education (FKIP) of the Syiah Kuala University (USK) which was dominated by women (only 2 men). According to the objectives, the study used a survey method and used an instrument in the form of a questionnaire containing 15 statements. Participants were asked to provide responses via google form by choosing true or false for each statement item on the questionnaire. The results of the analysis show that the understanding of the majority of students is quite good for macroscopic markers or indicators and low for sub-microscopic markers or indicators. Therefore, chemistry teachers need to use molecular (sub-microscopic) images when teaching materials or topics of physical and chemical changes.